Animasi Pembelajaran Adab dan Akhlak Sehari-hari Untuk Pendidikan Anak Usia Dini - Anggraini, Inda; Sasmita, Sasmita (Building of Informatics, Technology and Science (BITS), 2022)
The learning process that is currently taking place is still using conventional media, namely by using blackboard media and printed books so that it is still not optimal in increasing understanding of good manners and morals for students. In this way students pay less attention to explanations because they still have to learn while playing. This makes the teachers overwhelmed because they have to explain the material while the students are still in the stage of liking the game. The method used in this research is the development of the Analysis Design Development Implementation Evaluation (ADDIE) system. To measure the success rate of understanding daily etiquette and morals from students, a test instrument is used, namely the alpha testing instrument, namely expert review (experts) and beta which will later be in the form of pretest and posttest. The results obtained at this time is an application of learning etiquette and daily morality that has been tested using alpha and beta testing methods. Based on the results of the expert review that has been carried out, the results obtained are 4.1 in the Very Valid category. Furthermore, for the results of the field test, namely the alpha and beta tests obtained from the results of the pretest and posttest, the average student got 88 results in the high category. This indicates an increase in learning from students before and after the use of animation applications.